International cooperation against corruption in Uzbekistan and Turkey - Rakhmonaliyev Zikrullo Iqboljon ogli (The American Journal of Political Science Law and Criminology, 2025)
This article explores the issues of international cooperation in combating corruption in Uzbekistan and Turkey. It analyzes the national anti-corruption policies of these countries, their collaboration with international organizations, and the key challenges they face in this regard. As a result of the study, recommendations are proposed to strengthen cooperation between the two countries. International experiences and best practices in combating corruption are examined, and strategies relevant to Uzbekistan and Turkey are suggested.